Extensive mandible torus: bone density study, excision and histological findings - Rodrigues Azenha, Marcelo; Rodrigues, Giovani Antonio; Nabuo Bepu, Davi Ariel; Grupioni Lourenço, Alan; Aranha Watanabe, Plauto Christopher (Brazilian Journal of Case Reports, 2021)
Not applicable.